Eksplorasi Tantangan Pembelajaran Matematika di Kelas IX SMP N 45 Kota Bekasi - Ria Nur Indriasari (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This study aims to explore the challenges of mathematics learning in grade IX at SMP N 45 Kota Bekasi. The research method used is qualitative with a case study approach. Data were collected through interviews with teachers and students, as well as direct classroom observations. The findings show that the main challenges in mathematics learning include low student motivation, ineffective use of educational technology, and limited learning facilities. In addition, teaching methods that still rely on conventional approaches hinder students' understanding of mathematical concepts. This study recommends the use of more interactive teaching approaches and the utilization of technology to improve the quality of mathematics education at the school.